2011
DOI: 10.1159/000327357
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Plasma Cell Type of Castleman’s Disease and IgG4-Related Sclerosing Disease: A Histopathological and Immunohistochemical Study

Abstract: Objectives: Castleman’s disease (CD) is a group of rare atypical lymphoproliferative disorders classified as hyaline vascular (HV) and plasma cell (PC) types. CD may be closely mimicked by IgG4-related sclerosing disease (IgG4-SD) involving the lymph nodes. We retrospectively analyzed findings in patients with CD to elucidate the relationship between CD and IgG4-SD. Methods: Clinicopathological and immunophenotypical characteristics, including IgG+ and IgG4 expression by plasma cells, were analyzed in 87 conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
(10 reference statements)
1
4
0
Order By: Relevance
“…The diagnosis should be confirmed by histological examination, and traditionally three histological variants are distinguished. Castleman disease is closely mimicked by IgG4-related sclerosing disease, in Jo et al (2011). The conclusive diagnosis in our patient was Castleman like disease that is presented as autoinflammatory syndrome.…”
Section: Case Reportsupporting
confidence: 55%
“…The diagnosis should be confirmed by histological examination, and traditionally three histological variants are distinguished. Castleman disease is closely mimicked by IgG4-related sclerosing disease, in Jo et al (2011). The conclusive diagnosis in our patient was Castleman like disease that is presented as autoinflammatory syndrome.…”
Section: Case Reportsupporting
confidence: 55%
“…Pathologically, a number of studies had expounded the differences between IgG4-RD and CD. One study in Korean pathologically analyzed 87 CD patients and found that the mean IgG4+/IgG+ plasma cell ratio was 25.1% [15]. Sato et al [16] reported that the mean IgG4+/IgG+ plasma cell ratio was 57.6% in IgG4-RD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic IgG4-related lymphadenopathy could mimic the clinical signs of MCD. [ 23 25 ] Therefore, it is important to make a differential diagnosis between MCD and IgG4-RD. Although some patients with definite IgG4-RD show normal serum IgG4 concentrations, the elevation of serum IgG4 is more common in patients with IgG4-RD, and serum IgG4 levels ≥135 mg/dL is 1 of the major diagnostic criteria for IgG4-RD.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 29 ] However, an elevated serum IgG4 level is not specific for IgG4-RD as it can also be associated with non-IgG4-RDs, for example, hematological malignancies and allergic diseases, especially MCD with the PC or mixed variant. [ 23 25 ] However, higher levels of serum IL-6 and IgG, along with increases in IgM and/or IgA, and differences in the IgG4 + /IgG + ratio and morphological manifestations in the involved tissue [ 23 , 24 ] have been seen in MCD cases. Patients with IgG4-RD have elevated serum IgG4 levels, but most of them have normal levels or lower increases in serum IL-6.…”
Section: Discussionmentioning
confidence: 99%